Fire preventing and extinguishing material for inhibiting spontaneous combustion of coal pile as well as preparation method and application of fire preventing and extinguishing material
By spraying fire-fighting materials composed of fly mortar and composite colloids on the surface of the coal pile, the problems of fly mortar loss and reignition are solved, and high-efficiency oxygen isolation and water retention performance is achieved, cost reduction and improved the effect of self-ignition prevention and control of coal piles .
Patent Information
- Application Number
- CN202411095891.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, fly mortar is prone to loss and cannot effectively cover the fire zone, resulting in spontaneous combustion and rekindling of coal piles, and the cost is high.
Fire-proof and anti-extinguishing material composed of fly mortar and composite colloid. The composite colloid is composed of polymer polymer, active silicon micro powder, crosslinking agent, composite alkali exciter and water retention agent. The addition ratio is 0.3-1 wt%, and it is passed through the spraying device. Apply evenly on the surface of the coal pile to form a high-viscosity fly mortar, isolate oxygen and lock water to maintain moisture.
The long-term oxygen isolation and water retention properties of fire-fighting materials are achieved, the rapid loss of fly mortar water is avoided, the grouting cost is reduced, and the effect and durability of coal piles are improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal spontaneous combustion prevention and control, and specifically relates to a fire-proofing material for inhibiting spontaneous combustion of coal piles and a preparation method and application thereof. Background Art
[0002] In large coal-fired power plants, hundreds of thousands to hundreds of thousands of tons of coal must be stored to ensure normal production, and the storage period can be as long as several months. As the heat accumulation caused by slow oxidation leads to a gradual increase in temperature, these coal piles often spontaneously combust. According to statistics, after 6 months of storage, the heat loss of gas coal and long flame coal with a volatile content greater than 35% is an average of 4.9%, while the heat loss of lean coal with a volatile content less than 17% is an average of 2.0%. It can be seen that the spontaneous combustion of coal piles not only reduces the economic value of coal, but also the large amount of harmful gases produced by the spontaneous combustion of coal will directly pollute the atmosphere and seriously affect the regional ecological environment.
[0003] At present, the commonly used methods for preventing spontaneous combustion of coal piles in engineering practice include fine coal covering, wind barriers and windbreak walls, felt covering, coal pile compaction, fly ash slurry covering or blending, polymer inhibitors, hot rod technology, etc. Among them, the water in the fly ash slurry absorbs a lot of heat, which plays a role in extinguishing fire and cooling. The slurry covers the surface of the coal body and isolates the air. However, the fly ash slurry is easy to lose and cannot effectively cover the fire area, which is prone to re-ignition. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a fire extinguishing material for inhibiting spontaneous combustion of coal piles.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a fire-proof extinguishing material for inhibiting spontaneous combustion of coal piles, characterized in that: the fire-proof extinguishing material is composed of fly ash slurry and a composite colloid, the addition ratio of the composite colloid in the fly ash slurry is 0.3-1wt%, the fly ash slurry is composed of the following components in parts by weight: 80-100 parts of fly ash and 100 parts of water; the composite colloid is composed of the following components in parts by weight: 20-50 parts of high molecular polymer, 10-15 parts of active silicon powder, 3-5 parts of cross-linking agent, 2-5 parts of composite alkali activator, and 1-2 parts of water retaining agent.
[0008] As a preferred embodiment of the fire extinguishing material of the present invention, the high molecular polymer is one or more of sodium polyacrylate, polyacrylamide, sodium hydroxymethyl cellulose, sodium carboxymethyl cellulose, and the molecular weight of the high molecular polymer is 2 million to 30 million.
[0009] As a preferred embodiment of the fire extinguishing material of the present invention, the water retaining agent is a salt-resistant super absorbent resin, which has a water absorption rate of 300-700 g / g for tap water and a salt absorption rate of 106-150 g / g for physiological saline.
[0010] As a preferred embodiment of the fire extinguishing material of the present invention, the composite alkali activator is at least two of sodium sulfate, sodium sulfite, sodium hydroxide, sodium chloride and sodium carbonate.
[0011] As a preferred embodiment of the fire extinguishing material of the present invention, the composite alkali activator is composed of sodium carbonate, sodium sulfate and sodium hydroxide in a mass ratio of 5-6:8-10:2-4.
[0012] As a preferred embodiment of the fire extinguishing material of the present invention, the fly ash is primary fly ash.
[0013] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a fire extinguishing material for inhibiting spontaneous combustion of coal piles, which is characterized by comprising:
[0014] Make a slurry with water and fly ash at a weight ratio of 1:1 to 0.8, evenly add the composite colloid into the fly ash slurry, stir quickly to prevent agglomeration, and continue stirring for 1 minute after adding;
[0015] The composite colloid is added to the fly ash slurry in a proportion of 0.3 to 1 wt %;
[0016] Calculated by mass fraction, the components of the composite colloid include: 20-50 parts of high molecular polymer, 10-15 parts of active silicon powder, 3-5 parts of crosslinking agent, 2-5 parts of composite alkali activator, and 1-2 parts of water retaining agent.
[0017] As a preferred embodiment of the preparation method of the present invention, the rapid stirring has a stirring rate of 300 to 500 r / min.
[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a fire extinguishing material for inhibiting spontaneous combustion of coal piles.
[0019] As a preferred solution of the application of the present invention, the fire-proof extinguishing material covers and adheres to the surface of the coal pile to lock in moisture and isolate oxygen.
[0020] Beneficial effects of the present invention:
[0021] (1) The fire extinguishing material of the present invention uses fly ash, a solid waste from coal-fired power plants, as its main raw material. The fly ash slurry is used in combination with a high water-retaining composite colloid, which has a high solid-liquid ratio and greatly reduces the grouting cost.
[0022] (2) Good diffusion and filling properties: After adding the composite colloidal material of appropriate concentration, the fly ash slurry initially diffuses in the high-temperature coal body in the form of a slurry. After reaching the designed thickening time node, the fly ash slurry thickens rapidly, loses its self-fluidity, and forms a high-viscosity fly ash slurry to fill the air leakage gaps in the high-temperature area.
[0023] (3) Good adhesion and oxygen isolation properties: After adding appropriate concentrations of composite colloidal materials, the formed fly ash slurry can effectively cover and adhere to the surface of the coal pile, and has good oxygen isolation properties.
[0024] (4) Good water retention and stability: It can solidify the water in the fly ash slurry in the gel, has excellent thermal stability under high temperature environment, avoids the rapid loss of water in the fly ash slurry, and has a long-lasting effect. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0028] Unless otherwise specified, the raw materials described in the embodiments of the present invention are all commercially available products.
[0029] The fly ash described in the embodiment of the present invention is first-class fly ash produced by a coal-fired power plant.
[0030] The water-retaining agent described in the embodiment of the present invention is a salt-resistant super absorbent resin, which has a water absorption rate of 300-700 g / g for tap water and a salt absorption rate of 106-150 g / g for physiological saline.
[0031] The cross-linking agent in the embodiment of the present invention is a metal ion cross-linking agent, any one of aluminum chloride, aluminum sulfate, ferric chloride and ferric sulfate.
[0032] Example 1
[0033] (1) Prepare raw materials: A fire extinguishing material for inhibiting spontaneous combustion of coal piles, comprising fly ash slurry and a composite colloid, wherein the composite colloid is added to the fly ash slurry in a proportion of 0.3 wt %. The fly ash slurry is composed of the following components in parts by weight: 100 parts of fly ash and 100 parts of water; the composite colloid is composed of the following components in parts by weight: 30 parts of sodium polyacrylate (molecular weight 15 million to 30 million), 10 parts of active silicon powder, 3 parts of a cross-linking agent, 3 parts of a composite alkali activator, and 1 part of a water-retaining agent, salt-resistant super absorbent resin; wherein the composite alkali activator is composed of sodium carbonate, sodium sulfate, and sodium hydroxide in a mass ratio of 5:9:3.
[0034] (2) Use the mobile intelligent spraying device produced by Xuzhou Ji'an Mining Technology Co., Ltd. to spray the top and sides of the coal pile. Make a slurry with water and fly ash at a weight ratio of 1:1 to 0.8, add the composite colloid evenly to the prepared fly ash slurry, stir quickly to prevent agglomeration, and pass the mixed slurry into the spraying device for spraying.
[0035] Example 2
[0036] (1) A fire extinguishing material for inhibiting spontaneous combustion of coal piles, comprising fly ash slurry and a composite colloid, wherein the composite colloid is added to the fly ash slurry in a proportion of 0.5 wt %. The fly ash slurry is composed of the following components in parts by weight: 90 parts of fly ash and 100 parts of water; the composite colloid is composed of the following components in parts by weight: 40 parts of sodium polyacrylate (molecular weight 15 million to 30 million), 12 parts of active silicon powder, 4 parts of a cross-linking agent, 4 parts of a composite alkali activator, and 1 part of a water retaining agent; wherein the composite alkali activator is composed of sodium carbonate, sodium sulfate, and sodium hydroxide in a mass ratio of 5:9:3.
[0037] (2) Use the mobile intelligent spraying device produced by Xuzhou Ji'an Mining Technology Co., Ltd. to spray the top and sides of the coal pile. Make a slurry with water and fly ash at a weight ratio of 1:1 to 0.8, add the composite colloid evenly to the prepared fly ash slurry, stir quickly to prevent agglomeration, and pass the mixed slurry into the spraying device for spraying.
[0038] Example 3
[0039] (1) A fire extinguishing material for inhibiting spontaneous combustion of coal piles, comprising fly ash slurry and a composite colloid, wherein the composite colloid is added to the fly ash slurry at a ratio of 1 wt%. The fly ash slurry is composed of the following components in parts by weight: 80 parts of fly ash and 100 parts of water; the composite colloid is composed of the following components in parts by weight: 50 parts of sodium polyacrylate (molecular weight 15 million to 30 million), 15 parts of active silicon powder, 5 parts of a cross-linking agent, 5 parts of a composite alkali activator, and 2 parts of a water retaining agent; wherein the composite alkali activator is composed of sodium carbonate, sodium sulfate, and sodium hydroxide in a mass ratio of 5:9:3.
[0040] (2) Use the mobile intelligent spraying device produced by Xuzhou Ji'an Mining Technology Co., Ltd. to spray the top and sides of the coal pile. Make a slurry with water and fly ash at a weight ratio of 1:1 to 0.8, add the composite colloid evenly to the prepared fly ash slurry, stir quickly to prevent agglomeration, and pass the mixed slurry into the spraying device for spraying.
[0041] Example 4
[0042] (1) A fire extinguishing material for inhibiting spontaneous combustion of coal piles, comprising fly ash slurry and a composite colloid, wherein the composite colloid is added to the fly ash slurry in a proportion of 0.5wt%. The fly ash slurry is composed of the following components in parts by weight: 100 parts of fly ash and 100 parts of water; the composite colloid is composed of the following components in parts by weight: 35 parts of sodium carboxymethyl cellulose (molecular weight 8 million to 15 million), 12 parts of active silicon powder, 3.5 parts of a cross-linking agent, 2.5 parts of a composite alkali activator, and 1 part of a water retaining agent; wherein the composite alkali activator is composed of sodium carbonate, sodium sulfate, and sodium hydroxide in a mass ratio of 6:8:4.
[0043] (2) Use the mobile intelligent spraying device produced by Xuzhou Ji'an Mining Technology Co., Ltd. to spray the top and sides of the coal pile. Make a slurry with water and fly ash at a weight ratio of 1:1 to 0.8, add the composite colloid evenly to the prepared fly ash slurry, stir quickly to prevent agglomeration, and pass the mixed slurry into the spraying device for spraying.
[0044] Example 5
[0045] (1) A fire extinguishing material for inhibiting spontaneous combustion of coal piles, comprising fly ash slurry and a composite colloid, wherein the composite colloid is added to the fly ash slurry in a proportion of 0.8 wt %. The fly ash slurry is composed of the following components in parts by weight: 100 parts of fly ash and 100 parts of water; the composite colloid is composed of the following components in parts by weight: 45 parts of hydroxypropyl methylcellulose (molecular weight 2 million to 10 million), 14 parts of active silicon powder, 5 parts of a cross-linking agent, 4.5 parts of a composite alkali activator, and 2 parts of a water retaining agent; wherein the composite alkali activator is composed of sodium carbonate, sodium sulfate, and sodium hydroxide in a mass ratio of 5:10:2.
[0046] (2) Use the mobile intelligent spraying device produced by Xuzhou Ji'an Mining Technology Co., Ltd. to spray the top and sides of the coal pile. Make a slurry with water and fly ash at a weight ratio of 1:1 to 0.8, add the composite colloid evenly to the prepared fly ash slurry, stir quickly to prevent agglomeration, and pass the mixed slurry into the spraying device for spraying.
[0047] Example 6
[0048] This embodiment is to test the performance of the fire extinguishing materials prepared in Examples 1 to 5, specifically:
[0049] (1) The gel time test of fire extinguishing materials is as follows:
[0050] a) Use a measuring cylinder to measure 200 mL of water and pour it into a 500 mL beaker;
[0051] b) Weigh 200g of fly ash using an electronic balance, pour it into the above beaker, and stir evenly with a glass rod;
[0052] c) Weigh a certain proportion of the composite colloid and add it to the above slurry, stirring while adding. The consistency will slowly increase. Stop stirring when the slurry consistency stops increasing.
[0053] d) Let it stand for different periods of time, pour out the water from the upper layer, turn it upside down on the table, and measure the accumulation height.
[0054] (2) Water retention test of fire extinguishing materials: The specific method is: take 8-10 mg of composite colloidal material, use a thermogravimetric analyzer to test the water retention performance, heat from 25°C to 150°C, and the heating rate is 3°C / min, and record the residual mass at different temperatures.
[0055] (3) Thermal stability test of fire extinguishing materials: 100g of gel and water of the same weight are placed in a constant temperature drying oven and heated at a uniform rate within the temperature range of 100-190°C, and their weight loss rates are tested respectively.
[0056] Table 1 Performance test data
[0057] Gel time (min) Water retention (%) Example 1 45 >95% Example 2 40 >95% Example 3 30 >95% Example 4 41 >95% Example 5 33 >95%
[0058] It can be seen from Table 1 that the gelling time of the composite colloid is 30 to 45 minutes, which ensures that the fly ash slurry can diffuse in the high-temperature coal body in the slurry state at the initial stage, and the water retention rate is greater than 95%, indicating that the composite colloid prepared in the present application has good thermal stability and can solidify the water in the fly ash slurry in the gel, thereby avoiding the rapid loss of water in the fly ash slurry and having a long-lasting effect.
[0059] Comparative Example 1
[0060] The difference between this embodiment and embodiment 3 is that no cross-linking agent is added, and the remaining steps are the same as those in embodiment 3 to obtain a fire extinguishing material.
[0061] Comparative Example 2
[0062] The difference between this embodiment and embodiment 3 is that no composite alkali activator is added, and the remaining steps are the same as those in embodiment 3 to obtain a fire extinguishing material.
[0063] Comparative Example 3
[0064] The difference between this embodiment and embodiment 3 is that no water retaining agent is added, and the remaining steps are the same as those in embodiment 3 to obtain a fire extinguishing material.
[0065] The performance of the fire extinguishing materials prepared in Example 3 and Comparative Examples 1 to 3 was tested using the same testing method as in Example 6. The test results are shown in Table 2.
[0066] Table 2
[0067] Gel time (min) Water retention (%) Example 3 30 >95% Comparative Example 1 115 83% Comparative Example 2 91 85% Comparative Example 3 50 80%
[0068] Example 7
[0069] The difference between this embodiment and embodiment 3 is that sodium polyacrylate is replaced by polyacrylamide, and the remaining steps are the same as those in embodiment 3 to prepare the fire extinguishing material.
[0070] Comparative Example 4
[0071] The difference between this embodiment and embodiment 3 is that sodium polyacrylate is replaced by acrylamide, and the remaining steps are the same as those in embodiment 3 to prepare the fire extinguishing material.
[0072] Comparative Example 5
[0073] The difference between this embodiment and embodiment 3 is that the active silicon powder is replaced with white carbon black, and the remaining steps are the same as those in embodiment 3 to prepare the fire extinguishing material.
[0074] Comparative Example 6
[0075] The difference between this embodiment and embodiment 3 is that the composite alkali activator is replaced by sodium sulfate, and the remaining steps are the same as those in embodiment 3 to obtain a fire extinguishing material.
[0076] Comparative Example 7
[0077] The difference between this embodiment and embodiment 3 is that the active silicon powder is replaced by white carbon black, the composite alkali activator is replaced by sodium sulfate, and the remaining steps are the same as those in embodiment 3 to prepare the fire extinguishing material.
[0078] Comparative Example 8
[0079] The difference between this embodiment and embodiment 3 is that the composite alkali activator is composed of sodium carbonate, sodium sulfate and sodium hydroxide in a mass ratio of 4:5:1.
[0080] The performance of the fire extinguishing materials prepared in Examples 3, 7 and Comparative Examples 4 to 6 was tested using the same testing method as in Example 6. The test results are shown in Table 3.
[0081] Table 3
[0082] Gel time (min) Water retention (%) Example 3 30 >95% Example 7 32 >95% Comparative Example 4 No glue >95% Comparative Example 5 67 81% Comparative Example 6 73 86% Comparative Example 7 98 88% Comparative Example 8 56 92%
[0083] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A fire extinguishing material for suppressing spontaneous combustion of coal piles, characterized by: The fire extinguishing material is composed of fly ash slurry and composite colloid, and the addition ratio of the composite colloid to the fly ash slurry is 0.3-1wt%; The fly ash slurry is composed of the following components in parts by weight: 80-100 parts of fly ash and 100 parts of water; The composite colloid is composed of the following components in parts by weight: 20-50 parts of high molecular polymer, 10-15 parts of active silicon powder, 3-5 parts of crosslinking agent, 2-5 parts of composite alkali activator and 1-2 parts of water retaining agent.
2. The fire extinguishing material according to claim 1, wherein: The high molecular polymer is one or more of sodium polyacrylate, polyacrylamide, sodium hydroxymethyl cellulose, and sodium carboxymethyl cellulose, and the molecular weight of the high molecular polymer is 2 million to 30 million.
3. The fire extinguishing material according to claim 1, wherein: The water-retaining agent is a salt-resistant superabsorbent resin, which has a water absorption rate of 300-700 g / g for tap water and a salt absorption rate of 106-150 g / g for physiological saline.
4. The fire extinguishing material according to claim 1, wherein: The composite alkali activator is at least two of sodium sulfate, sodium sulfite, sodium hydroxide, sodium chloride and sodium carbonate.
5. The fire extinguishing material according to claim 4, characterized in that: The composite alkali activator is composed of sodium carbonate, sodium sulfate and sodium hydroxide in a mass ratio of 5-6:8-10:2-4.
6. The fire extinguishing material according to claim 1, wherein: The fly ash is first-grade fly ash.
7. The method for preparing a fire extinguishing material for suppressing spontaneous combustion of coal piles according to any one of claims 1 to 6, characterized in that: include, Mix water and fly ash in a weight ratio of 1:1 to 0.8 to make a slurry. Evenly add the composite colloid into the fly ash slurry and stir quickly to prevent agglomeration. Continue stirring for 1 minute after adding. The addition ratio of the composite colloid to the fly ash slurry is 0.3-1 wt%; Calculated by mass fraction, the components of the composite colloid include: 20-50 parts of high molecular polymer, 10-15 parts of active silicon powder, 3-5 parts of crosslinking agent, 2-5 parts of composite alkali activator, and 1-2 parts of water retaining agent.
8. The preparation method according to claim 7, wherein: The rapid stirring, wherein the stirring rate is 300-500 r / min.
9. Use of the fire extinguishing material for suppressing spontaneous combustion of coal piles as claimed in any one of claims 1 to 6 in preventing and controlling spontaneous combustion of coal piles.
10. The use according to claim 9, characterized in that: The fire-proof extinguishing material covers and adheres to the surface of the coal pile to lock in moisture and isolate oxygen.
Citation Information
Cited By
Inorganic gel fire preventing and extinguishing material for preventing and controlling spontaneous combustion of coal and preparation method of inorganic gel fire preventing and extinguishing material
CN121060043A
Fireproofing material for inhibiting spontaneous combustion of coal pile and application thereof
CN123024283A
